The relationship between Parental Level of Education and Learners Performance in Public Pre -Primary schools in Nandi County, Kenya. - Chemagosi, Mary Jebii (International Journal of Scientific Research and Management (IJSRM), 2020)
AbstractFactors related with parental involvement on their childrens education continues to be a pertinent issue. Some school going children in Kenya post detrimental results amid claims that parents are not supportive. This study sought to establish influence of Parental Level of Education on Pre-PrimaryLearners performance in curriculum activities in Nandi County, Kenya. Epsteins Theory and descriptive survey design was used for the study. Purposive sampling technique, stratified random technique and simple random technique were used to select the sample of the study. The sample for the study was 50 head teachers 100 teachers and 100 parents in pre-Primary schools from a population of 500 head teachers, 1000 teachers and 10000 parents. Questionnaire, interview guides and focused group discussions were used to collect data. A pilot study was conducted in two schools to determine the validity and reliability of instruments. Both content and face validity were ensured while split half technique was used to determine the instrument’s reliability. Quantitative data was analyzed using descriptive such as frequencies and percentages and presented in form of tables while inferential statistics used simple linear regression. Qualitative data was analyzed and presented in narrative form.